2016
DOI: 10.1016/j.actamat.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural stability and mechanical behavior of FeNiMnCr high entropy alloy under ion irradiation

Abstract: In recent years, high entropy alloys (HEAs) have attracted significant attention due to their excellent mechanical properties and good corrosion resistance, making them potential candidates for high temperature fission and fusion structural applications. However there is very little known about their radiation resistance, particularly at elevated temperatures relevant for energy applications. In the present study, a single phase (face centered cubic) concentrated solid solution alloy of composition 27%Fe-28%Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
139
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 510 publications
(167 citation statements)
references
References 110 publications
8
139
2
Order By: Relevance
“…However, the temperature dependence in the FeNiMnCr 0.66 is less significant compared with the conventional Fe-Cr-Ni alloys. Moreover, considerably higher loop density and lower loop size have been reported in FeNiMnCr 0.66 , compared with those in the conventional Fe-Ni-Cr alloys (Kumar et al, 2016). Furthermore, higher fraction of faulted loops have been observed in the more compositionally complex alloys, indicating that increasing compositional complexity can extend the incubation period and delay loop growth .…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 89%
See 3 more Smart Citations
“…However, the temperature dependence in the FeNiMnCr 0.66 is less significant compared with the conventional Fe-Cr-Ni alloys. Moreover, considerably higher loop density and lower loop size have been reported in FeNiMnCr 0.66 , compared with those in the conventional Fe-Ni-Cr alloys (Kumar et al, 2016). Furthermore, higher fraction of faulted loops have been observed in the more compositionally complex alloys, indicating that increasing compositional complexity can extend the incubation period and delay loop growth .…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 89%
“…Unlike in Lu et al (2016b), no voids have been observed in both cases at all the test temperatures. For the observable defect clusters, the density decreases but the size increases with increasing irradiation temperature (Kumar et al, 2016;Yang et al, 2018). However, the temperature dependence in the FeNiMnCr 0.66 is less significant compared with the conventional Fe-Cr-Ni alloys.…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 97%
See 2 more Smart Citations
“…[1,2]. It is widely used for semiconductor doping in micro-and nanoelectronics, medicine [3,4], space, chemical and aviation industries [5][6][7][8][9]. The main advantages of ion implantation are preservation of sample sizes, locality (small projective path), high reproducibility, absence of problems with adhesion etc.…”
Section: Introductionmentioning
confidence: 99%